Some anthropometric measurements in athletes and non-athletes among students in Medan - Laksamana Aulia Laksamana Aulia (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1986)
To study the possibility of the influence of exercise on body posture, anthropometric measurements were taken in 40 male athletes and 41 male non-athletes, as well as in 26 female athletes and 24 female non-athletes, among students in Medan. The measurements included height, weight, arm and thigh circumferences, thorax diameters, and skinfold thickness. The results showed that there was a significant difference in the left arm circumference between male athletes and male non-athletes, whereas in the female none of the measurements taken showed any significant difference. The explanation of these results has to be sought by further studies with more consideration on the types of exercise performed. Key Words: arm and thigh circumferences - thorax diameters - skinfold thickness - athletes - anthropometry